Por uma linguística (mais) popular: a construção do gênero neutro como dissidência linguística - Gomes, Robert Moura Sena (2022)
With the effervescence of social movements, the understanding that a language is also a place where the identity of a collectivity is anchored has made it also an object of struggle. With the advent and intensification of the use of the internet, and markedly of online social networks, new forms of organization of socially underprivileged groups (indigenous community, women, blacks, LGBTQIAPN+, and people with disabilities, for example) have become more evident. Regarding the use of gender-neutral as a form of recognition and representation of the LGBTQIAPN+ community in social spaces, including the language itself, it was found that there is linguistic dissidence - a concept proposed in this dissertation - as a possibility of subversion, in this case, of the linguistic system. As a consequence, several linguists and popular linguists have also positioned themselves in a plural and diverse way about the discursive procedures that act in the relationship or not between the grammatical category of gender and gender identities. The analyzed texts were written by professional linguists (scientific knowledge) and by non-linguists (popular knowledge) starting from the hypothesis, which was approached and proven, that it is in the continuum between the scientific and the popular that there are disagreements and agreements, both concerning the validation of the knowledge of popular linguists, as concerning the proposals raised for the (re)formulation of the linguistic aspect as a marker of gender in the Portuguese language of Brazil. To this end, we are guided by the studies developed by Folk/Popular Linguistics (ALBURY, 2017; MURILLO, 2008; PAVEAU, 2007; 2018; 2021; PRESTON, 1993; 1994), which proposes that the knowledge of non-linguists is important and must be observed and integrated into scientific studies, as well as in the proposals of Discourse Analysis (FOUCAULT, 2014).